2018
DOI: 10.1155/2018/6459364
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions on Diet and Dietary Modifications during Postpartum Period Aiming at Attenuating Progression of GDM to DM: A Qualitative Study of Mothers and Health Care Workers

Abstract: Background Gestational diabetes mellitus (GDM) is a global concern. GDM mothers have a 7-fold relative risk of developing type 2 diabetes mellitus (T2DM) in their later life. User-friendly and culturally acceptable dietary interventions can minimize this risk. Therefore, this study aims at exploring the perceptions of GDM mothers and health care workers regarding factors that influence postpartum dietary practices aimed at attenuating the trajectory from GDM to DM. Methods The study was conducted in selected M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 32 publications
2
33
0
Order By: Relevance
“…Twenty‐five studies reported on women's perspectives and three on HPs' perspectives. Ten studies were conducted in United States, 32–41 six in Australia, 42–47 three in United Kingdom, 48–50 two each in Hawaii 51,52 and Netherlands 53,54 and one each in New Zealand, 55 Canada, 56 Norway, 57 Mexico 58 and Sri Lanka 59 . Seven studies reported on women who had previously had high risk pregnancies including gestational diabetes mellitus (GDM), pre‐eclampsia and postnatal depression.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty‐five studies reported on women's perspectives and three on HPs' perspectives. Ten studies were conducted in United States, 32–41 six in Australia, 42–47 three in United Kingdom, 48–50 two each in Hawaii 51,52 and Netherlands 53,54 and one each in New Zealand, 55 Canada, 56 Norway, 57 Mexico 58 and Sri Lanka 59 . Seven studies reported on women who had previously had high risk pregnancies including gestational diabetes mellitus (GDM), pre‐eclampsia and postnatal depression.…”
Section: Resultsmentioning
confidence: 99%
“…Lacking knowledge on when to safely resume exercise after childbirth and the health consequences of pregnancy complications were barriers for postpartum women especially in those who had a pregnancy complicated by GDM or pre‐eclampsia 44,49,54 . Similarly, HPs believed that women were unaware of the benefits of physical activity, the importance of postpartum dietary modifications and weight control in reducing future risk of type 2 diabetes 50,58,59 . In one study, HPs themselves reported lacking knowledge of the relationship between GDM and diabetes mellitus (DM) and the role of dietary habits in the progression of GDM to DM 59 …”
Section: Resultsmentioning
confidence: 99%
“…64,65 Following childbirth, the woman's focus shifts from her health to her child's well-being. 47,66 The reprioritization to child and family commitments over personal health creates challenges for mothers in making time for exercise or preparing healthy meals for themselves. 53,[66][67][68] Family members could pose a further barrier by being unsupportive of healthy meals.…”
Section: Motivationmentioning
confidence: 99%
“…47,66 The reprioritization to child and family commitments over personal health creates challenges for mothers in making time for exercise or preparing healthy meals for themselves. 53,[66][67][68] Family members could pose a further barrier by being unsupportive of healthy meals. 51,68 Cultural or self-derived expectations also lead to postpartum women feeling guilty taking time out for selfcare.…”
Section: Motivationmentioning
confidence: 99%
“…Whilst invitation to the study was done by doctors not involved in this research, the study sample from both urban and rural population was generally representative of women with GDM in this region. Moreover, the sample size was su cient to provide saturation of themes (20). However, fewer women were recruited from SLH, and all these women were interviewed during prenatal period.…”
Section: Strengths and Limitationsmentioning
confidence: 99%